2019
DOI: 10.2147/ijn.s212807
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel nanomaterial-based antibacterial photodynamic therapies to combat oral bacterial biofilms and infectious diseases</p>

Abstract: Oral diseases such as tooth caries, periodontal diseases, endodontic infections, etc., are prevalent worldwide. The heavy burden of oral infectious diseases and their consequences on the patients’ quality of life indicates a strong need for developing effective therapies. Advanced understandings of such oral diseases, e.g., inflammatory periodontal lesions, have raised the demand for antibacterial therapeutic strategies, because these diseases are caused by viruses and bacteria. The application of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 136 publications
0
100
0
Order By: Relevance
“…Some noble or heavy metal nanoparticles, including gold, copper, and silver nanoparticles exhibit an interesting localized surface plasmon resonance (LSPR) effect under visible light irradiation [ 29 ]. It was reported that the generated surface plasmons are effective to provide photodynamic killing of bacteria [ 30 ]. If taking the much smaller size and vulnerability of viruses into consideration, these metal nanoparticles with the surface plasmon effect would also be effective against viral infection under normal visible light irradiations.…”
Section: Antiviral Surfaces and Coatingsmentioning
confidence: 99%
“…Some noble or heavy metal nanoparticles, including gold, copper, and silver nanoparticles exhibit an interesting localized surface plasmon resonance (LSPR) effect under visible light irradiation [ 29 ]. It was reported that the generated surface plasmons are effective to provide photodynamic killing of bacteria [ 30 ]. If taking the much smaller size and vulnerability of viruses into consideration, these metal nanoparticles with the surface plasmon effect would also be effective against viral infection under normal visible light irradiations.…”
Section: Antiviral Surfaces and Coatingsmentioning
confidence: 99%
“…PDT was used as an antimicrobial strategy to inhibit biofilms formed by a broad spectrum of microorganisms by effectively damaging the cell membrane within the biofilm in vitro (Wood et al, 1999 ). Subsequently, antimicrobial PDT was found to nonspecifically attack microorganisms by generating cytotoxic ROS, which have strong oxidation ability and high reactivity, thus causing rapid lipid oxidation of the bacteria (Qi et al, 2019 ). It has been found that the antibiofilm activity of PDT is also associated with inhibition of the ability of microorganisms to adhere to surfaces, destroying biofilm structures, damaging some organelles, inducing virulence factor secretion, and inhibiting efflux capacity and QS (Arciola et al, 2011 ; Li et al, 2017 ; Tan et al, 2018 ; Hendiani et al, 2019 ; Mahdizade-Ari et al, 2019 ).…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%
“…Most antibiofilm studies of PDT have used this technique for dental plaque-related diseases and chronic wound infections (Zanin et al, 2005 ; Dilsiz et al, 2013 ; Mahmoudi et al, 2019 ); however, some studies have also used PDT to combat biofilm-related infections in ventilator-associated pneumonia and chronic rhinosinusitis (Krespi and Kizhner, 2011 ; Geralde et al, 2017 ). A majority of photosensitizers are poorly soluble in water and hydrophobic; however, with the application of NMs, this limitation might be overcome (Qi et al, 2019 ). PDT has emerged during the era of nanotechnology, and these combination strategies have been shown to have good effects (Khan et al, 2012 ).…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feature of structural variability is beneficial to wide application in different fields through the design of holes and skeletons, such as semiconduction, photoconductor, gas adsorption and storage, diagnoses, and treatment (Wan et al, 2008(Wan et al, , 2009Fang et al, 2015;Huang et al, 2016;Mitra et al, 2017;Zhu and Zhang, 2017). Recently, nanomaterial-based antibacterial photodynamic therapy gradually gained increasing attention (Qi et al, 2019). The antibacterial photodynamic therapy bases on the interaction of harmless nanosized-photosensitizers, tissue oxygen, and visible light to yield high level of ROS, which has a strong oxidation and high reactivity, thus causing rapid lipid oxidation of the bacteria.…”
Section: Nanomaterials With Inherent Antibacterial Activitymentioning
confidence: 99%